Injuries pattern and heart rate variation in elite judo athletes: A Korean prospective cohort study - Park, K. J.; Jeong, D. N. (Science & Sports, 2022)
Objectives To report injury patterns in elite judo athletes expected to represent Korea in future Olympics and investigate their relationship with heart rate variation. Methods From 2018, we prospectively collected data on elite judo athletes at the Korean Training institute. The athletes were assessed by sports medicine doctors, and data were stratified according to sex, weight class, and injury location. We used Chi2 tests to compare groups. Injury rates were expressed as Poisson rates with 95% confidence intervals. The measuring equipment used was an autonomic neurodiagnostic device (SA-6000), Measurements were recorded concerning: heart rate, total power, low frequency, high frequency and low frequency/high frequency ratio, the was measured. One-way analysis of variance was used to investigate the injury incidence rates and heart rate variation. Results The study included 213 elite judo athletes whose 593 injuries (annual average, 2.78 injuries/athlete) were recorded. In general, injury rate was similar between the lightweight and heavyweight classes. When all athletes were considered, most injuries occurred in the lower extremities (38.79%), followed by the upper extremities (30.69%), trunk (23.44%), and head and neck area (7.08%). Injury severity was significantly different among the weight classes, and body regions. The association between injury incidence rates was statistically significant in total power and low frequency. Conclusion Heart rate variation was found to affect injury incidence. Low total power and low frequency increased the risk of sports injury. Our findings can facilitate the development of injury prevention programs for elite judo athletes and help improve performance.